Fintech Lending Adoption among Muslim Millinials in Southeast Asia - Safira, Nabila; Inayatillah; Meutia, Rachmi; Kamri, Nor ‘Azzah; Yusof, Ku Abdulmuhaimin (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2025)
This article discusses how economic, social, and cultural factors simultaneously influence the interest in using online loans among the millennial Muslim generation in Banda Aceh. The purpose of this study is to determine the economic, social, and cultural factors simultaneously influencing the interest in using online loans among the millennial Muslim generation in Banda Aceh. The research method uses a quantitative research method. The data source used in this study is primary data. Data obtained from the first data source at the research location, both individuals and companies, obtained through filling out questionnaires or interviews. In the data collection technique, this study uses a questionnaire method. In this study, filling out the questionnaire in the form of questions that are given a value weight using a likert scale. The results of this study indicate that the economic factor variables (X1) and social factors (X2) have a positive and significant influence on the use of online loans among the millennial Muslim generation in Banda Aceh City, while the cultural factor variable shows that it has a negative and significant influence.